Propuesta de sistema de adquisición y transmisión de datos compatible con el SCADA Ovation en la planta geotérmica Las Pailas - Sánchez-Chaves, Juan Carlos (Instituto Tecnológico de Costa Rica, 2018)
The project was developed in the Costa Rican Institute of Electricity (ICE), in the Geothermal Resources Service Center (CSRG), at the Instrumentation Maintenance Department, which is in charge of the maintenance and repair of instrumentation equipment in SCADA´s of the geothermal fields Miravalles and Las Pailas. The controller in charge of the acquisition and transmission of data in the platform 1 of the Las Pailas plant was damaged as a result of an electric shock during a lightning strike at the end of 2016, so there was no monitoring of head and line pressures. In the three active wells, the Ovation system used in Las Pailas with OCR400 controllers in each of the platforms, was oversized for the functions performed and its high price prevented the purchase of the spare part, there is no permanent staff in the site, so both the production in the square was stopped. In this project, the Ovation OCR400 controller was replaced by a data acquisition system implemented in an Allen-Bradley 1769-L18ER-BB1B controller and instrumentation in 4-20 mA HART. Communication was also established between the Allen-Bradley 1769-L18ER-BB1B controller and the SCADA Ovation platform, in charge of automatic control, storage and visualization of the data in the plant, thus preserving the format used for the monitoring of the platforms.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Control; Adquisición; Datos; PLC; PAC; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics